In service inspections of thick walled concrete sructures - Pecinka, L.; Moravka, S. (Проблемы прочности, 2006)
Ageing management and renewal of the operating license of existing NPP’s are at present the main problems of nuclear power industry. For the ageing management of concrete structures the OECD-Nuclear Energy Agency, Committee on the Safety on Nuclear Installations defined as the first priority ISI techniques for reinforced concrete structures having thick sections and areas not directly accessible for inspections. We discuss the NRI Rez research and development program in this field, as well as results, which will be used for qualification of the ISI techniques.